2016
DOI: 10.1016/j.ebiom.2016.05.008
|View full text |Cite|
|
Sign up to set email alerts
|

One of the immune activation profiles observed in HIV-1-infected adults with suppressed viremia is linked to metabolic syndrome: The ACTIVIH study

Abstract: Immune activation in HIV-1-infected individuals is reduced under antiretroviral therapies, but persists, resulting in various morbidities. To better characterize this phenomenon, using a panel of 68 soluble and cell surface markers, we measured the level of activation in circulating CD4+ and CD8+ T cells, B cells, monocytes, NK cells, polynuclear and endothelial cells as well as of inflammation and fibrinolysis in 120 virologic responders over 45 years of age. As compared with age- and sex-matched uninfected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 68 publications
4
28
0
Order By: Relevance
“…Chronic immune activation and insulin resistance can contribute to obesity, dyslipidemia, CVDs, and non-alcoholic fat liver disease (NAFLD) as well as neurocognitive disorders, metabolic disorders, bone abnormalities, and non-HIV associated cancers ( 12 , 97 , 98 , 99 ). While the evolution of these complications depends on genetic and environmental factors, each condition has the potential of aggravating another (Figure 2 ).…”
Section: Consequences Of Immune Activation and Insulin Resistance Inmentioning
confidence: 99%
“…Chronic immune activation and insulin resistance can contribute to obesity, dyslipidemia, CVDs, and non-alcoholic fat liver disease (NAFLD) as well as neurocognitive disorders, metabolic disorders, bone abnormalities, and non-HIV associated cancers ( 12 , 97 , 98 , 99 ). While the evolution of these complications depends on genetic and environmental factors, each condition has the potential of aggravating another (Figure 2 ).…”
Section: Consequences Of Immune Activation and Insulin Resistance Inmentioning
confidence: 99%
“…The Strategies for the Management of Antiretroviral Therapy (SMART) study demonstrated that plasma levels of interleukin-6 (IL-6), C-reactive protein, and D-dimer are independent predictors of mortality in HIV infection, including deaths related to cardiovascular disease (CVD) ( Kuller, LH, et al, 2008 , Emery, S, et al, 2008 ). The predictive value of markers of immune activation and inflammation has been confirmed in several studies ( Psomas, C, et al, 2016 , Hunt, PW, et al, 2014 , Kalayjian, RC, et al, 2010 ). Potential mechanisms have also been identified that may contribute to increased activation of both the innate and the adaptive immune systems in chronic HIV infection, including: copathogens, microbial translocation, pro-inflammatory lipids, low level viral replication, and the immune system's response to cytopenia ( Lederman et al, 2013 ).…”
mentioning
confidence: 74%
“…In their manuscript in EBioMedicine , Psomas and colleagues used a combination of 68 markers of immune activation and inflammation and two independent hierarchical clustering analyses to identify 5 donor groups from among 120 HIV-infected virologic responders ( Psomas et al, 2016 ). These donor groups were characterized using combinations of activation markers among CD4 + T cells, CD8 + T cells (CD38, HLA-DR, CD279, CD57), B cells (serum levels of IgG, IgA, IgM) natural killer cells (HLA-DR, CD69), monocytes (soluble CD14 and sCD163), and markers of inflammation and coagulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antiretroviral therapy (ART) extends the lifespan and the quality of life of HIV-infected patients while completely eliminating chronic immune activation and inflammation does not occur ( 3 , 4 ). Persistent inflammation contributes to immune senescence and exhaustion, factors linked to most non-AIDS-related complications of HIV, such as cardiovascular, neurocognitive, and metabolic syndromes ( 2 5 ). A comprehensive understanding of the molecular and cellular basis of the inflammatory status allows these remaining challenges of HIV treatment to be addressed.…”
Section: Introductionmentioning
confidence: 99%